2019
DOI: 10.1002/ppul.24566
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal lung ultrasonography score after surfactant in preterm infants: A prospective observational study

Abstract: ObjectiveTo assess changes in neonatal lung ultrasonography score (nLUS) after surfactant administration in preterm infants with respiratory distress syndrome (RDS).Working HypothesisThe reduction of nLUS score before (nLUSpre), 2 hours (nLUS2h), and 12 hours (nLUS12h) after surfactant administration to identify patients who will not need a second treatment.Study Design and SettingProspective observational study in the tertiary neonatal intensive care unit.Patients SelectionForty‐six preterm neonates with RDS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 27 publications
4
52
0
Order By: Relevance
“…It was 39.4% (n ¼ 13) in the mild RDS group and 100% (n ¼ 12) in the severe RDS group. The patients achieved a median maximum FiO 2 level of 35% (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) when the first dose of surfactant was administered and had a 50% reduced need for oxygen after the treatment (considering a response to treatment as reduction of at least 20% of the previous FiO 2 level). The LUS score median value on admission to the NICU was 5 (2-10) and the SaO 2 /FiO 2 ratio was 161 (148-310).…”
Section: Resultsmentioning
confidence: 99%
“…It was 39.4% (n ¼ 13) in the mild RDS group and 100% (n ¼ 12) in the severe RDS group. The patients achieved a median maximum FiO 2 level of 35% (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) when the first dose of surfactant was administered and had a 50% reduced need for oxygen after the treatment (considering a response to treatment as reduction of at least 20% of the previous FiO 2 level). The LUS score median value on admission to the NICU was 5 (2-10) and the SaO 2 /FiO 2 ratio was 161 (148-310).…”
Section: Resultsmentioning
confidence: 99%
“…This study showed that in preterm infants with RDS a LU score 2 hours after surfactant administration can be useful in identifying patients who will need a second treatment. In particular, a score greater than or equal to 7 showed a sensitivity of 94%, a specificity of 60%, a NPV of 95%, and a PPV of 56%.⁠ 46 …”
Section: Lu As Semiquantitative Techniquementioning
confidence: 93%
“…A recent paper published by Perri et al 46 explored the change in LU score after 2 hours from surfactant administration. The score utilized divided the chest into the same areas as the score by Brat et al 41 with minimal changes on attribution of the score for a single area.…”
Section: Lu As Semiquantitative Techniquementioning
confidence: 99%
“…by Quarato et al and we are pleased by the interest directed to our article "Neonatal lung ultrasonography score after surfactant in preterm infants: A prospective observational study" published on your journal. 1 This study included preterm neonates with respiratory distress syndrome (RDS) who required noninvasive ventilation and surfactant. The aim of our study was to assess changes in a validated neonatal lung ultrasonography score (nLUS) after surfactant treatment.…”
Section: E T T E R T O T H E E D I T O R Neonatal Rds and Lus Is Tmentioning
confidence: 99%